Activation of the sigma-1 receptor exerts cardioprotection in a rodent model of chronic heart failure by stimulation of angiogenesis - Xin Zhao; Xin Liu; Xiuhuan Chen; Xueyu Han; Yazhou Sun; Yuhong Fo; Xiukun Wang; Chuan Qu; Bo Yang (BMC, 2022)
Abstract Background Angiogenesis plays a critical role on post-infarction heart failure (PIHF), the presence of which facilitates additional blood supply to maintain the survival of residual cardiomyocytes. The sigma-1 receptor (S1R) has been substantiated to stimulate angiogenesis, with the effect on a model of PIHF remaining unknown. Aims This study aims to investigate the effects of S1R on PIHF and the underlying mechanisms involved. Methods Rats were implemented left anterior descending artery ligation followed by rearing for 6 weeks to induce a phenotype of heart failure. Daily intraperitoneal injection of S1R agonist or antagonist for 5 weeks was applied from 2nd week after surgery. The effects exerted by S1R were detected by echocardiography, hemodynamic testing, western blot, Sirius red dyeing, ELISA, immunohistochemistry and fluorescence. We also cultured HUVECs to verify the mechanisms in vitro. Results Stimulation of S1R significantly ameliorated the cardiac function resulted from PIHF, in addition to the observation of reduced fibrosis in the peri-infarct region and the apoptosis of residual cardiomyocytes, which were associated with augmentation of microvascular density in peri-infarct region through activation of the JAK2/STAT3 pathway. We also indicated that suppression of JAK2/STAT3 pathway by specific inhibitor in vitro reversed the pro-angiogenic effects of S1R on HUVECs, which further confirmed that angiogenesis, responsible for PIHF amelioration, by S1R stimulation was in a JAK2/STAT3 pathway-dependent manner. Conclusion S1R stimulation improved PIHF-induced cardiac dysfunction and ventricular remodeling through promoting angiogenesis by activating the JAK2/STAT3 pathway.